A IDENTIDADE DO CURRÍCULO DA EDUCAÇÃO DE JOVENS E ADULTOS: OLHARES DOCENTES E DISCENTES - Keller, Lenir (2020)
Youth and Adult Education (EJA in Portuguese acronym) as a modality of Basic Education is intended for those who have not had access or continuity of studies in elementary and high school, at adequate school age. The institutionalization of the modality in the Federal Constitution and the Law of Guidelines and Bases of National Education No. 9394/96 was marked by advances in terms of conception, but with challenges and weaknesses regarding the implementation, the scope, the methodology, the curricular proposals, the teacher training, the financing and the infrastructure, in order to ensure the provision of appropriate educational opportunities, respecting the characteristics of students, interests, living and working conditions. In view of this, the Youth and Adult Education curriculum has been the topic of studies in order to build an approximation with its subjects and their expectations of formation. Thus, the general objective of this study was to investigate the identity of the Youth and Adult Education curriculum and its materialization in teaching practices in schools of the Municipal Education System of Santa Maria – RS, considering its constitution, specificity and purposes. The methodology adopted was qualitative, based on literature review, documentary analysis, and data were searched through a field research, with the application of questionnaires, using the principles of hermeneutics for analysis and interpretation of the informations. The research corpus involved six regent teachers and 12 students, six enrolled and six graduates, from 12 schools that offer the EJA. The problematization about the school curriculum dealt with questions concerning the students' initial expectations and their school experiences, the relevance of the knowledge covered and the contributions of the modality to their education. As for the teachers, considerations were raised about continuing education, achievements and frustrations in teaching in the modality, their vision and impressions about the school curriculum. It was found that curricular identity runs through the articulation between basic formation and preparation for the world of work, but it requires a flexible organization of times, differentiated methodologies, the revitalization of teacher training processes, improvement in the infrastructure of schools and increased investments to qualify the offer of the modality.